Image of U.S. presidential administrations : the cases of George W. Bush and Barack Obama - Calca, Patrícia, 1979-; Belim, Célia (Lexington Books, 2013)
This book analyzes the image of the U.S. presidential administrations from 2001 to 2011 and their political image in foreign countries. The authors focus on the European perception of U.S. presidencies, specifically during the terms of George W. Bush and Barack Obama. Political image is decisive in electoral victory and, more often, is central in the conquest and maintenance of political power. Political image is also highly relevant because of the credibility of the United States on the international stage, resulting in gained confidence and the celebration of profitable alliances. This study of political image has a crucial interdisciplinary framework fordisciplines such as communication, political science, and international relations.